Preserving Microbial Biodiversity: The Case of Food-Associated Microorganisms - Spiros Paramithiotis; Maria Dimopoulou (Ecologies, 2023)
The preservation of microbial diversity is an issue not properly addressed, considering their role in shaping Earth into a habitable planet and their contribution to human well-being. The disturbance of their natural habitats triggers responses, which are reflected in the modification of microecosystem composition and metabolic activities. This is also the case with food-related microecosystems; changes in the growing environment, recorded as agricultural practices and manufacturing or storage conditions, result in similar alterations in the residing microcommunity. In fact, the principle aim of food microbiology is to favor the growth of health-promoting microorganisms and restrict the development of the ones that may negatively affect the quality of food or even cause infection or intoxication. Therefore, the current perspective is one-sided, disregarding issues of general interest, such as the preservation of actual biodiversity. The aim of the present article is to present the current food microbiology perspective, which is based on the different roles of food-related microbiota and highlight the need to move from an anthropocentric to a microbe-centric perception.